Development of Learning Media Assisted Adobeflash CS7 by Using the Demonstration Method in Science Learning - Riqqah Annisa Maharani; Yeni Erita; Darmansyah Darmansyah; Elfia Sukma (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this project is to create an Adobe Flash CS7 application-assisted learning resource for science instruction in class IV of an elementary school. Development research was the method adopted in this study. The phrase "research and development" is used. The analysis, design, development, implementation, and evaluation phases of the ADDIE model are used in this work. The 40 students who make up the study's subjects are instrument validators, class IV students at public elementary school 01 Sawahan and class IV students at public elementary school 05 Sawahan. A questionnaire was employed in this development research to gather information from media professionals, material experts, and students in order to evaluate the learning media that were being created. To gauge students' motivation for learning, questionnaires of their responses are employed. Validity analysis, which examines the applicability of learning medium, is the method of data analysis applied. The generated learning materials were proven to be reliable and useful for usage in primary classrooms. Learning materials created with the Adobe Flash CS7 program are acceptable for use in grade IV elementary schools while teaching science. An average validity score of 3.71 is obtained, falling into the very valid group. The practicality test results demonstrated that the created product was usable, with an average value of 88.25 falling into the very practical category